Sonographer credentialing in extended focussed assessment by sonography in trauma (eFAST). Issue 2 (7th May 2019) - Cormack, Carolynne J.; Lavender, Ilona; Coombs, Peter R.; Ptasznik, Ronnie
Abstract: Introduction: Sonographers of a large, metropolitan health service were trained and credentialed in extended focussed assessment by sonography in trauma in preparation for a potential mass casualty incident. Given the prior ultrasound experience of this cohort, the suitability of an abbreviated credentialing pathway based upon that required for emergency physicians was evaluated. Method: A training and credentialing process to teach extended focussed assessment by sonography in trauma was planned for sonographers. The model was based upon existing credentialing requirements for emergency physicians. The project was undertaken in two stages, using a "train the trainer" approach. The initial stage trained and credentialed a group of senior sonographer trainers. This group then supported the training and credentialing of the wider sonographer cohort. Results: Twenty‐eight qualified sonographers were successfully trained and credentialed in extended focussed assessment by sonography in trauma scanning. Practical competency assessment demonstrated 100% (28/28) pass rate. Image interpretation assessment results also demonstrated 100% (28/28) pass rate. Conclusion: An abbreviated model is suitable for the training and credentialing of sonographers in extended focussed assessment by sonography in trauma, given their pre‐existing ultrasound skills and knowledge.